Iatrogenic esophageal perforation in infants: how to avoid thoracotomy? Two case reports - Riccardo Rizzo; Filomena Valentina Paradiso; Sara Silvaroli; Lorenzo Nanni (EL-Med-Pub, 2023)
Background: Esophageal perforation is uncommon and often iatrogenic in the neonatal period, and premature and low birth weight infants (<1500 g) are particularly susceptible. Esophageal injury in neonates usually occurs at the pharyngoesophageal junction and can be confused with esophageal atresia due to respiratory signs and excessive salivation. Diagnostic evaluation and treatment are still debated.  Case Presentation: This case report aims to describe two neonatal cases of iatrogenic esophageal perforation. The suspected diagnosis was confirmed only with thoracotomy. Diagnostic difficulties and therapeutic modalities are discussed.  Conclusion: These two cases show the importance of the clinical clues (anamnesis and clinical findings) to suspect the diagnosis of esophageal perforation.